2019
DOI: 10.1177/0003489419837565
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Postradiation Dysphagia in Head and Neck Cancer Patients: A Systematic Review

Abstract: Objectives: To systematically review the success rate and safety profile of the available endoscopic surgical options for radiation-induced dysphagia in head and neck cancer patients following organ preservation treatment, including upper esophageal sphincter (UES) dilation, cricopharyngeus (CP) myotomy (CPM), and CP intramuscular botulinum toxin (Botox) injection. Methods: A search of MEDLINE, Scopus, Google Scholar, and Cochrane databases was done to identify articles published between January 1980 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Despite the lack of high-quality studies, there is some evidence to justify the use of UES myotomy in HNC patients. UES myotomy significantly improved swallowing outcomes of HNC patients with OD following organ preservation therapy [362]. Research by Silver and colleagues also revealed recovery of OD in 90% of their HNC patients following CO2 laser myotomy of a post-(C) RT stenosis at the UES level [368].…”
Section: Surgical Treatment Of Oropharyngeal Dysphagia In Head and Nementioning
confidence: 92%
See 3 more Smart Citations
“…Despite the lack of high-quality studies, there is some evidence to justify the use of UES myotomy in HNC patients. UES myotomy significantly improved swallowing outcomes of HNC patients with OD following organ preservation therapy [362]. Research by Silver and colleagues also revealed recovery of OD in 90% of their HNC patients following CO2 laser myotomy of a post-(C) RT stenosis at the UES level [368].…”
Section: Surgical Treatment Of Oropharyngeal Dysphagia In Head and Nementioning
confidence: 92%
“…Since 1951, studies have reported several surgical and less-invasive treatments for UES dysfunction. The effectiveness of each treatment in the management of OD, due to various etiologies including HNC and its oncological treatment, is still subject to debate [362][363][364][365]. A malfunctioning UES can be diagnosed as described under previous sections of this paper (see "Videofluoroscopic swallow study" and "Manometry").…”
Section: Surgical Treatment Of Oropharyngeal Dysphagia In Head and Nementioning
confidence: 99%
See 2 more Smart Citations
“…CP achalasia, failure of the CP to relax, may be idiopathic or result from gastroesophageal reflux disease, among other etiologies. 4…”
mentioning
confidence: 99%